Distress to Heal: Psychological Distress terhadap Sikap Pencarian Bantuan Profesional Psikologis pada Emerging Adult - Pinkan Fadhilah; Lia Mawarsari Boediman (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
As the prevalence of psychological distress continues to rise, the study aimed to explore the relationship between psychological distress and attitude towards seeking profesional psychological help among emerging adults in Indonesia. Out of 180 participants, regression analyses revealed no significant relationships between psychological distress and attitudes towards seeking profesional psychological help. Notably, 43.4% of participants had very high psychological distress, while 83.9% had positive attitudes towards seeking profesional psychological help. These results highlight the intricate connections between psychological distress and attitudes towards seeking profesional help, along with the influence of other factors. Covariate analyses indicated significant associations with gender, the perceived need for help, and stigma in others. The study emphasizes the need for further research to investigate the role of culture underlying this relationship.